2016
DOI: 10.1001/jamaophthalmol.2016.3519
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Insights Into Choroidal Vascular Loss in Clinically Documented Cases of Age-Related Macular Degeneration

Abstract: IMPORTANCE-Age-related macular degeneration (AMD) is a multifactorial disease with genetic and environmental factors contributing to risk. Histopathologic changes underlying AMD are not fully understood, particularly the relationship between choriocapillaris (CC) dysfunction and phenotypic variability of this disease.OBJECTIVE-To examine histopathologic changes in the CC of eyes with clinically documented AMD. DESIGN, SETTING, AND PARTICIPANTS-The study was designed in 2011. Tissues were collected post mortem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
152
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(166 citation statements)
references
References 31 publications
11
152
0
1
Order By: Relevance
“…29 Previous histologic studies have reported choriocapillaris loss underlying drusen, occurring very early in disease pathogenesis, 30,31 as well as reduced choroidal vessel density and diameter with advanced AMD. 32–34 Prior studies also reveal discordant results in evaluating the relationship between subfoveal choroidal thickness and advanced AMD.…”
Section: Discussionmentioning
confidence: 97%
“…29 Previous histologic studies have reported choriocapillaris loss underlying drusen, occurring very early in disease pathogenesis, 30,31 as well as reduced choroidal vessel density and diameter with advanced AMD. 32–34 Prior studies also reveal discordant results in evaluating the relationship between subfoveal choroidal thickness and advanced AMD.…”
Section: Discussionmentioning
confidence: 97%
“…In early AMD, Seddon et al recently found that choriocapillaris loss, using EC-binding lectin from Ulex europaeus (UEA-I) to distinguish live from ghost vessels, preceded RPE cell atrophy (Seddon et al, 2016). The Mullins laboratory, also using UEA-I, found that loss of choriocapillaris area and an increase in ghost vessels, correlated with increased drusen size and density, implicating a role for choriocapillaris dysfunction in drusenogenesis (Mullins et al, 2011).…”
Section: Histopathologic Changes In Non-neovascular Amdmentioning
confidence: 99%
“…Several studies have focused mainly on the level of the retina's outer layers, including the photoreceptors [4,5], the retinal pigment epithelium (RPE), Bruch's membrane (BM) [6][7][8][9], and the choroid [10,[11][12][13]. However, drusen [14][15][16][17], essential for the classification and monitoring of AMD [10,15], are the main alteration at the beginning of this degenerative process [18,19].…”
Section: © 2017 S Karger Ag Baselmentioning
confidence: 99%